Evaluación del Estrés laboral en los trabajadores de la Empresa SERVISILVA de la Provincia de Orellana en el período 2024 - Galvez Otavalo, Paola Andrea (2025)
Work-related stress is a significant problem that affects every individual physically or mentally. High unemployment rates, economic instability, family problems, and interpersonal issues have caused people, especially workers, to be even more affected by these sudden changes, leading them to face constant stressful situations. We began by sharing the content of the test that was administered to workers at the company Servisilva Cia Ltda. This is a cross-sectional and descriptive study. The study population consisted of 88 workers, including managers from different areas, using the questionnaire developed by Dr. Cristina Villalobos. SPSS V27 statistical software was used to process the data. To conclude the study, an intervention manual was developed for the most critical factors. The results obtained were 4 workers with low stress, 79 with medium stress, and 5 with high stress. It was concluded that the variable investigated has a medium-high impact on stress, with alarming symptoms that are concerning for workers' health. Therefore, it is necessary to mitigate these symptoms through support strategies, improved working conditions, a collaborative work environment, and positive psychology, among other actions that can create a healthier and safer environment for workers.